Use of mesoporous silica as a reinforcing agent in rubber compounds (2005)
ABSTRACT: esoporous silica is used as filler for styrene-butadiene rubber (SBR); filler-polymer interactions are compared with those exhibited when Ultrasil silica (VN3) is used. A silane coupling agent is added to improve filler dispersion and its influence on the bound-rubber formation is also investigated. The bound-rubber content is higher for the mesoporous silica and increases further for the sample containing silane. The increase is explained by chemical interactions between filler and rubber and penetration of the rubber chains into the mesopores. This is confirmed by 13C solid-state NMR, IR spectroscopy and differential scanning calorimetry. Dynamic mechanical thermal analysis shows higher storage modulus for the rubber filled with mesoporous silica.